Faktor-Faktor yang Mempengaruhi Perilaku Seksual Pernikahan Berisiko Kehamilan Tidak Diinginkan pada Mahasiswa Di Kota Jombang - Mudrikatin, Siti; Setyowati, Risha (LPPM STIKES HUSADA JOMBANG, 2022)
Adolescents are the future of the nation, who will play a role in continuing development, but are in a turbulent transition period and have the risk of unwanted pregnancy. The purpose of this study was to determine the factors that influence the sexual behavior of marriage at risk of unwanted pregnancy in students in Jombang City. The research method was carried out on adolescents who were studying at universities in the city of Jombang. This is a quantitative study with a cross sectional approach, the population is 362 respondents aged 18 - 24 years, the data collection method is using a questionnaire. Bivariate test and multivariate test with logistic regression were used to find out whether there was an effect of the independent variable and the dependent variable. The results of the study of variables that affect sexual behavior in marriages at risk of unwanted pregnancy are attitudes towards sexuality and self-efficacy, where students who have a more permissive attitude have a risk of premarital sexual behavior at risk of unwanted pregnancy. The conclusion of marital sexual behavior at risk of unwanted pregnancy shows that 11.9% admit to committing. Suggestions for increasing information and understanding on students not having sex with sex education, sexually transmitted diseases, the risk of unwanted pregnancy so that cross-sectoral and cross-program collaboration is needed with the government as policy makers.